Pelatihan Arduino kepada Remaja Mushola Ka’bah dengan Tema: “Santri Berdikari, Mandiri Teknologi” - Ikhwan Taufik; Hilmy, Fuad (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Al Iman is a prayer room with a unique shape like the Kaaba and have an ancient handwritten Al Qur'an by Syech Al Basyin in ancient times. Even though there are these privilege, it turns out that the time markers in the Al Iman prayer room are only limited to wall clocks. The problem is, Al Iman is relatively small, has just been built, and haven't enough cash to allocate to procuring digital prayer time markers (focus on completing construction). Meanwhile, local youth have a high learning spirit and the surrounding community looks very enthusiastic. This is proven by the existence of the Mushola Youth Association and the routine "reciting Al Qur'an" which is carried out every night after praying together. Therefore, the solution offered is the holding of learning activities or "ngaji" (training). However, "ngaji" in this time is about of technology especially the basics of microcontroller programming. Hope can add insight into digital technology and microcontroller programming, especially Arduino Uno as a basis for making microcontroller-based digital clocks. Furthermore, an understanding of digital technology and microcontroller programming which is applied in the form of digital clocks marking prayer times is displayed and used in the Mushola.